2008
DOI: 10.3989/gya.2008.v59.i2.505
|View full text |Cite
|
Sign up to set email alerts
|

<i>Sterculia striata</i> seed kernel oil: Characterization and thermal stability

Abstract: RESUMENAceite de almendra de la semilla de Sterculia striata: Caracterización y estabilidad térmica.El objetivo de este trabajo fue la caracterización del aceite de almendra de la semilla de Sterculia striata. Se determinaron la composición química, las propiedades químico-fí-sicas, composición en ácidos grasos, así como la estabilidad térmica de la harina (polvo) de almendra. La composición química de la harina contiene cerca de 25,8% de lípidos, los parámetros químico-físicos, tales como: índice de acidez, y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(1 citation statement)
references
References 9 publications
(8 reference statements)
0
0
1
Order By: Relevance
“…The protein content of chicha varies according to the region of its cultivation. In the present study, the water content of the soil was higher than that previously observed for other regions (Rocha et al, 2013;Diniz et al, 2008). Fruits from different regions may present different centesimal compositions, due to differences in soil characteristics, fertilization, climate and other environmental factors (Silva & Fernandes, 2011).…”
Section: Introductioncontrasting
confidence: 68%
“…The protein content of chicha varies according to the region of its cultivation. In the present study, the water content of the soil was higher than that previously observed for other regions (Rocha et al, 2013;Diniz et al, 2008). Fruits from different regions may present different centesimal compositions, due to differences in soil characteristics, fertilization, climate and other environmental factors (Silva & Fernandes, 2011).…”
Section: Introductioncontrasting
confidence: 68%